2018
DOI: 10.2116/analsci.34.177
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Highly Sensitive Quantitation of Eicosanoids in Biological Samples Using Nano-flow Liquid Chromatography/ Mass Spectrometry

Abstract: A simple sample preparation method for eicosanoid was developed by the combination of deproteinization and nanoLC-ESI-MS/MS. Eicosanoids are a group of bioactive lipid mediators, present in trace amounts in the body. Therefore, an analytical method for eicosanoids requires superior sensitivity. The method described in this report, which takes advantage of the highly sensitive power of nanoLC-ESI-MS/MS, enabled a simplification of the sample-preparation process. Eicosanoid extraction was performed just by homog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In clinical chemistry, blood-based lipid biomarkers for obesity are crucial for the diagnosis of the disease. Moreover advanced LC/MS techniques were widely applied for lipid biomarker discovery in various models 26,27 . In the present study, a rodent rat model was used, and rats were fed with ND and HFD (fat source: HF-L-lard) for 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical chemistry, blood-based lipid biomarkers for obesity are crucial for the diagnosis of the disease. Moreover advanced LC/MS techniques were widely applied for lipid biomarker discovery in various models 26,27 . In the present study, a rodent rat model was used, and rats were fed with ND and HFD (fat source: HF-L-lard) for 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of the developed method is the simultaneous evaluation of a wide range of metabolites from CYP450, a poorly explored pathway. Many studies are focused primarily on COX and LOX pathway 34–36 . However, the balance between the CYP450 pathway and these other vias may be decisive for the global understanding of a biological phenomenon or elucidating a specific phenomenon in an immunological condition.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, LOQ values in a range of 10–50 ng/L have been reported for eicosanoid analysis using nano-LC–MS/MS in different biological tissues . Ando and Satomi demonstrated that the SP procedure can be minimized due to the higher sensitivity of nano-LC–MS/MS compared to other LC–MS/MS platforms (HPLC or even UHPLC) …”
Section: Lipidomicsmentioning
confidence: 99%